System of monitoring and management of electricity consumption in the micro-energy system of a territorial community with own sources - Usenko, S.; Ponomarenko, E.; Kaplun, R.; Ivashchuk, V. (Energy and Automation, 2025)
The article considers the practical aspect of organizing the functioning of a microgrid of a housing cooperative of household owners as a prototype for implementing European principles of decentralized energy supply in accordance with the new Law of Ukraine "On the Electricity Market".The study deals with the analysis of the features of structuring microenergy system sources and the principles of implementing monitoring and management of electricity consumption based on the use of modern software and hardware complexes.The advantages of using cloud technologies (Oracle) for data processing, forming electricity consumption balances and forecasting in real time are proven.The authors investigated the possibilities of integrating heterogeneous generation sources (external network, diesel generator, solar power plants, electricity storage systems) into a single microgrid with the ability to operate both when connected to the external network and in isolated mode (in energy island mode) with its own metering and dispatching system. Ways for further development of micro-energy systems of territorial communities in Ukraine are proposed, taking into account European experience and current regulatory and legal support.Key words: microgrid, energy island, decentralized energy supply, monitoring system, electricity consumption management, power balancing